Peer-to-Peer Lending's Influence on Bank Performance: Core Capital Perspectives : Pengaruh Pinjaman Antar Rekan terhadap Kinerja Bank: Perspektif Modal Inti - Chaerani Nisa; Irma Sari Permata; Mulyadi; Syafira Ahyani (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
The study intends to evaluate the influence of peer-to-peer lending (P2P lending) on banks performance, focusing on differences in core capital classifications. Using data from the Financial Service Authority and Bank Indonesia websites, the analysis spans the fourth quarter of 2021 to the third quarter of 2023. The results reveal that P2P lending negatively affects bank performance, with more significant adverse impacts observed in banks with lower core capital, categorized under KBMI 1 and 2, compared to KBMI 3 and 4. These findings underscore the need for regulatory policies tailored to address the vulnerabilities of smaller banks, including measures to promote consolidation and capital augmentation. This study offers valuable insights into the interplay between financial technology and banking regulations, providing practical implications for policymakers and stakeholders.